2020
DOI: 10.3390/ijms21041346
|View full text |Cite
|
Sign up to set email alerts
|

p53-Related Transcription Targets of TAp73 in Cancer Cells—Bona Fide or Distorted Reality?

Abstract: Identification of p73 as a structural homolog of p53 fueled early studies aimed at determining if it was capable of performing p53-like functions. This led to a conundrum as p73 was discovered to be hardly mutated in cancers, and yet, TAp73, the full-length form, was found capable of performing p53-like functions, including transactivation of many p53 target genes in cancer cell lines. Generation of mice lacking p73/TAp73 revealed a plethora of developmental defects, with very limited spontaneous tumors arisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 126 publications
0
13
0
Order By: Relevance
“…The complex phenotype of the Trp73 deficient mice have revealed that p73 function is essential for the organization and homeostasis of different complex microenvironments governing various aspects of tissue physiology. Altogether, this has raised the idea that TAp73 was not evolved for tumor suppression, but rather to perform unique functions in regulating developmental processes through p53-independent mechanisms (Wang et al, 2020). We propose that some of the, apparently unrelated, phenotypes observed in Trp73 −/− mice are the reflection of the p73 requirement for the establishment and/or maintenance of tissue organization (Figure 4).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The complex phenotype of the Trp73 deficient mice have revealed that p73 function is essential for the organization and homeostasis of different complex microenvironments governing various aspects of tissue physiology. Altogether, this has raised the idea that TAp73 was not evolved for tumor suppression, but rather to perform unique functions in regulating developmental processes through p53-independent mechanisms (Wang et al, 2020). We propose that some of the, apparently unrelated, phenotypes observed in Trp73 −/− mice are the reflection of the p73 requirement for the establishment and/or maintenance of tissue organization (Figure 4).…”
Section: Discussionmentioning
confidence: 94%
“…The discovery of the TA-and DN-p73 isoforms with antagonist anti-and pro-oncogenic functions, and the TAp73KO mice predisposition to spontaneous tumorigenesis, demonstrated TAp73 role as a tumor suppressor gene (Tomasini et al, 2008). However, there is growing evidence indicating that while TAp73 has a role in tumor suppression, it is likely to be secondary (reviewed in Wang et al, 2020). The complex phenotype of the Trp73 deficient mice have revealed that p73 function is essential for the organization and homeostasis of different complex microenvironments governing various aspects of tissue physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, p63 has value in identifying malignancy and for tumour classification, and isoform‐specific ΔNp63 antibodies are superior to assessing total p63 in many situations (reviewed in ref 249). In addition, although not well studied in clinical material, TAp63 provides prognostic information [15,18,249–251] and requires more study in lymphomas and lymphocytes (including tumour‐infiltrating lymphocytes) to understand its prognostic impact and opportunities for therapy. Advances in understanding p63 isoforms and their regulation will inevitably lead to new diagnostic, prognostic and therapeutic opportunities for cancer and other pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their well-demonstrated roles in DDR and apoptosis ( Wilhelm et al, 2010 ), p73 isoforms also have unique targets ( Logotheti et al, 2019 ; Wang et al, 2020 ) and exert non-oncogenic functions ( Inoue et al, 2014 ) that are not shared with p53. Understanding their functional pleiotropy has been enabled through the use of DNp73 splice isoform-specific antisense oligonucleotide gapmers ( Emmrich et al, 2009 ) and by knockout mice models with (i) deletion of the entire TP73 gene, (ii) deletion of exons encoding the TAp73 isoforms, (iii) deletion of exons encoding the ΔNp73 isoform, and (iv) deletions of exons encoding the C-terminus of the alpha isoform.…”
Section: The Expanding Functional Repertoire Of Tp73 In Cancer and Beyondmentioning
confidence: 99%